Plan de marketing social para promover el uso de mosquiteros impregnados en el sector La Baldramina alta, cantón Quevedo, año 2015 - Álvarez Merelo, Oscar Lenin (2015)
This research “Social Marketing Plan to promote the use of impregnated mosquito nets" had place in the field of High Baldramina, Quevedo town, province of Los Ríos, Ecuador, during the year 2015. The overall objective of the research was "Develop social marketing plan to promote the use of impregnated bednets in the sector of high Baldramina, Quevedo town". This research began with the following problem: "How can a plan of social inform and promote marketing, as appropriate, the use of impregnated bed nets (ITN), to the public of the sector of high Baldramina, San Camilo Parish, Quevedo town?" With respect to the habits of disease prevention of malaria and dengue, the research found that a large majority of respondents covers the containers that hold water in your home; 53% empty containers, cans, tires, etc., that contain standing water in your yard or surrounding areas; a highly significant majority, if you have well or cistern, purifies chlorine and lid; an almost complete most do not know the art of preventing disease malaria and dengue, called impregnated awnings; 83% expressed intent of knowledge of how to prepare an impregnated sheet; Tv channels preferred are: O.Q Tv. Channel 35, and King Tv. 39. Chanel favorite shows are the news; 46% prefer to listen Viva radio, radio satellite follows RVT, preferred radio programs are news and sports. The specific hypotheses were tested positively. Strategies of Marketing-Mix Social considered: Price (the set of communication tools), Plaza (adopters of the High Baldramina sector), promotion (distribution channels with direct and indirect means: Public Relations, Social Media, neighborhood committees, and Strategic Partners) and advertising (TV, radio, social networking and….